(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2025)
In today's digitalized world devastated by natural disasters, accidents and catastrophes, the issue of using software applications for the purpose of monitoring and prevention of areas with a high risk of disasters and catastrophes is gaining increasing importance. The purpose of the study is to analyze the regulatory documents regulating critical infrastructure sites and activities for their identification, reporting and protection. The article presents the relationship between the national legislation of the Republic of Bulgaria and the legislation of the European Union regarding the risks of disasters and catastrophes. Using the methods of scientific research as a systematic and scientific analysis, a review of the regulatory documents regulating the protection of critical infrastructure and the possibilities for visualizing the risk of disasters and catastrophes through GIS software applications is carried out. The conclusions of the research show the need for a wider introduction and use of GIS-based software applications with free access, which would allow for the visualization of the risk of disasters in the critical infrastructure sites of the European Union countries. Integrating the collected information into a platform at a European level will enable member states to predict and manage the risks of disasters and catastrophes, which will lead to better advance planning and saving human lives.